Evolution of Anisotropic Coal Permeability Under the Effect of Heterogeneous Deformation of Fractures - Li, Jianhua; Li, Bobo; Cheng, Qiaoyun; Gao, Zheng (Natural resources research (New York, N.Y.), 2021)
Permeability is one of the key parameters to better understand the processes of coalbed methane mining and carbon dioxide geological storage. As a unique porous medium, coal usually possesses distinct deformation characteristics. In this work, we used a cubic model to characterize the physical structure of coal. The fracture system in coal contained both soft and hard parts subject to the natural-strain-based Hooke law and engineering-strain-based Hooke law, respectively. By analyzing the changes in the soft and hard parts of fractures, we explored heterogeneous deformation in coal. However, coal usually exhibits strong anisotropy under reservoir conditions, and the permeability in each direction is different. First, based on the generalized Hooke law, we characterized fracture deformation in coal along all directions under stress. Moreover, based on the definition of the coal porosity, we proposed an anisotropic coal permeability model under heterogeneous fracture deformation, and the model was verified against experimental data reported in the literature. Second, based on our proposed model, we examined the influence of the soft/hard parts of fractures on permeability, and the contribution of gas adsorption to the coal permeability was also analyzed. When the confining pressure remained constant, a higher proportion of the soft parts of fractures corresponded to a larger permeability change, and a higher internal expansion factor corresponded to a lower permeability. In addition, we assessed the influence of slippage on the permeability in the effective stress change process and incorporated the slippage effect into the permeability model.